2004
DOI: 10.1044/1058-0360(2004/023)
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rating of Stuttering Severity as a Clinical Tool

Abstract: Scaling is a convenient and equipment-free means for speech-language pathologists (SLPs) and clients to evaluate stuttering severity in everyday situations. This study investigated the extent to which the severity ratings of 10 adult stuttering speakers, made immediately after speaking and again from recordings 6 months later, agreed with ratings made by an SLP. For 9 of the 10 speakers, there was good agreement between their initial ratings and those of the SLP. For 8 of the 10 speakers, there was also good a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 24 publications
1
30
1
Order By: Relevance
“…Participants rated the severity of their stuttering on a 9-point scale (1 = "no stuttering", 9 = "extremely severe stuttering"). Self-reported severity ratings have been shown to correlate with the severity ratings of speech-language pathologists in adults in the clinic (O'Brian, Packman, & Onslow, 2004) but this has not been demonstrated for the age groups in this study. However, self-rating provides a socially valid indication of stuttering severity in the real world and is appropriate for use in this study as participants' responses to the RCMAS were also self-generated.…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…Participants rated the severity of their stuttering on a 9-point scale (1 = "no stuttering", 9 = "extremely severe stuttering"). Self-reported severity ratings have been shown to correlate with the severity ratings of speech-language pathologists in adults in the clinic (O'Brian, Packman, & Onslow, 2004) but this has not been demonstrated for the age groups in this study. However, self-rating provides a socially valid indication of stuttering severity in the real world and is appropriate for use in this study as participants' responses to the RCMAS were also self-generated.…”
Section: Methodsmentioning
confidence: 72%
“…Further research could investigate the extent to which self-reported severity ratings in children and adolescents correlate with the severity ratings of speech-language pathologists, similar to the study of O'Brian et al (2004) with adults.…”
Section: Interpretation Of High Lie Scale Scoresmentioning
confidence: 95%
“…This scale has been used successfully as a reliable overall measure of stuttering severity in previous research (O'Brian et al, 2011;O'Brian, Packman, & Onslow, 2004). Self-rated stuttering severity was assessed using a unipolar 9-point Likert scale with ratings averaged across eight different speaking situations and higher scores indicating more severe physical stuttering.…”
Section: Methodsmentioning
confidence: 99%
“…O'Brian, Packman and Onslow (2004) previously demonstrated that this scale is a reliable tool for self-evaluation of stuttering severity for 8 of 10 clients studied. In the present study, participant self-ratings were recorded immediately following the recording of oral reading and monologue samples in both the No Device and Device conditions.…”
Section: Speech Measuresmentioning
confidence: 96%